2016
DOI: 10.1515/johh-2016-0036
|View full text |Cite
|
Sign up to set email alerts
|

Projected changes of rainfall event characteristics for the Czech Republic

Abstract: Projected changes of warm season (May-September) rainfall events in an ensemble of 30 regional climate model (RCM) simulations are assessed for the Czech Republic. Individual rainfall events are identified using the concept of minimum inter-event time and only heavy events are considered. The changes of rainfall event characteristics are evaluated between the control (1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) and two scenario (2020-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
0
15
1
Order By: Relevance
“…In particular, we study the slopes of the 0.05-0.95 quantiles in steps of 0.05 (see Figure 1). This builds upon the results of Moberg et al (2006), who partitioned precipitation distribution in 2%, 5%, 10%, 90%, 95%, and 98% percentiles and calculated the corresponding trends, and Allan and Soden (2008), Rossow et al (2013), Svoboda et al (2016Svoboda et al ( , 2017 who considered discrete 5-10% quantile bins, in a comparison between observed data and model simulations.…”
Section: Methodsmentioning
confidence: 84%
“…In particular, we study the slopes of the 0.05-0.95 quantiles in steps of 0.05 (see Figure 1). This builds upon the results of Moberg et al (2006), who partitioned precipitation distribution in 2%, 5%, 10%, 90%, 95%, and 98% percentiles and calculated the corresponding trends, and Allan and Soden (2008), Rossow et al (2013), Svoboda et al (2016Svoboda et al ( , 2017 who considered discrete 5-10% quantile bins, in a comparison between observed data and model simulations.…”
Section: Methodsmentioning
confidence: 84%
“…However, recent values of the erosivity index were not exceptional when compared to a longer (91-year) record available at a single station. Considerable projected increases in the rainfall erosivity index in an ensemble of regional climate model simulations for the Czech Republic were reported by Svoboda et al (2016b).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that extreme rainfall changes for the Iberian Peninsula are different from those in other regions. For instance, some studies have found evidence of increasing trends in intensity for various European regions, with the Czech Republic being an example [27].…”
Section: Discussionmentioning
confidence: 99%